The resilient practitioner : burnout and compassion fatigue prevention and self-care strategies for the helping professions - Skovholt, Thomas M.; Trotter-Mathison, Michelle (Oxon : Routledge, 2016)
"The Resilient Practitioner, 3rd edition, gives students and practitioners the tools they need to create their own personal balance between caring for themselves and caring for others. This new edition includes a new chapter on resiliency, an updated self-care action plan, self-reflection exercises in each chapter, and a revised resiliency inventory for practitioners. Readers will find, however, that the new edition keeps its strong focus on research and accessible writing style. The new edition also retains its focus on establishing working alliances and charting a hopeful path for practitioners, a path that allows them to work intensely with human suffering and also have a vibrant career in the process."--
Keywords: Medical personnel--Mental health; Psychotherapists--Mental health; Burn-out (Psychology)--Prevention.